2020
DOI: 10.1002/jobm.202000430
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of physicochemical and biochemical properties of natural and arginine‐modified melanin from medicinal mushroom Ganoderma lucidum

Abstract: Melanin is a hydrophobic biomolecule produced widely in fungi. Compared with other fungi, health benefits have been associated with medicinal mushrooms, which may provide an excellent source of natural melanin. Nevertheless, the hydrophobicity of melanin may limit its applications. Consequently, the present study was carried out on isolation of melanin from the medicinal mushroom Ganoderma lucidum (GLM) and modification with arginine to improve its solubility. The physicochemical and biochemical properties of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…The purified melanin samples were modified with L-arginine following Xu et al (2020) with some modifications. Based on our previous study, the arginine was mixed with F. fomentarius melanin in a ratio of 1:1 (w/w) and 1:1.5 (w/w) with D. tricolor melanin, and then dissolved in 5 mL of distilled water.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The purified melanin samples were modified with L-arginine following Xu et al (2020) with some modifications. Based on our previous study, the arginine was mixed with F. fomentarius melanin in a ratio of 1:1 (w/w) and 1:1.5 (w/w) with D. tricolor melanin, and then dissolved in 5 mL of distilled water.…”
Section: Methodsmentioning
confidence: 99%
“…Fortunately, initial studies found that melanin modification with amino acids could enhance their water solubility and subsequently, some of their bioactivities. For example, modification of fungal melanin with either arginine or glucosamine increased the anti-radiation, antioxidant, and antitumor activities of the samples ( Ye et al, 2012 ; Song et al, 2016 ; Li et al, 2018 ; Shi et al, 2018 ; Xu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The second melanin pathway is named the L-DOPA pathway after L-3,4-dihydroxyphenylalanine [27]. There is more DOPA-type melanin in edible mushrooms, such as G. lucidum [28], Termitomyces albuminosus [29], A. bisporus [30], and Auricularia auricula [31]. We found only one polyphenol oxidase gene in I. obliquus, but A. bisporus had four genes (Table S11).…”
Section: Melanin Biosynthesis Involved In Polyketide Synthasementioning
confidence: 97%
“…[15] Natural fungus melanin has arose concern because of its biological activities, such as scavenging free radicals, preventing radiation, and binding heavy metal ions. [19][20][21] A previous study obtained melanin from a rice medium of I. hispidus and found that it has antioxidant activity in vitro. [15] However, there are no reports on the protection mechanisms of the liver by melanin from I. hispidus fruiting bodies (IHFM).…”
Section: Introductionmentioning
confidence: 99%